HUBUNGAN DUKUNGAN KELUARGA DENGAN KECEMASAN PADA PASIEN RAWAT LUKA DIABETES DI KLINIK HUSADA JOMBANG - Fatmawati, Istiadah; Ayun, Sofa Qurrata; Kristiana, Ike; Siswati, Eny (LPPM STIKES HUSADA JOMBANG, 2024)
Diabetes mellitus is a chronic disease that can cause complications in the form of diabetic wounds. Patients with diabetic wounds require intensive care and can cause anxiety. Family support plays an important role in reducing patient anxiety. The aim of this study was to analyze the relationship between family support and anxiety in patients treating diabetes wounds at the Husada Jombang Clinic. This study used a cross-sectional design involving 100 patients treating diabetic wounds at the Husada Jombang Clinic. Data collection was carried out using a family support questionnaire and an anxiety questionnaire. Data were analyzed using the Pearson correlation test. The results showed that there was a significant relationship between family support and anxiety in diabetic wound care patients (p<0.001, r=-0.657). The higher the family support, the lower the patient's anxiety level. Family support has an important role in reducing anxiety in diabetic wound care patients. Therefore, the role of the family in providing emotional, informational, instrumental and assessment support needs to be increased to help patients manage anxiety during diabetes wound care.